29.8k views
4 votes
Solve the equation
50=4(x-7)-6(3x-6)

2 Answers

2 votes

50 = 4(x - 7) - 6(3x - 6)

Apply the Distributive Property to get rid of the parentheses first. The Distributive Property: a(b + c) = ab + ac.

50 = 4(x - 7) - 6(3x - 6)

50 = 4x - 28 - 18x + 36

Collect like terms (constants and x-terms).

50 = 4x - 28 - 18x + 36

50 = -14x + 8

Subtract 8 from both sides to isolate the variable term.

42 = -14x

Divide both sides by -14 to isolate x.

42/-14 = -14x/-14

-3 = x

Answer:

x = -3

User Tyler Scott
by
4.4k points
7 votes

we are given


50=4(x-7)-6(3x-6)

Firstly , we can distribute


50=4x-28-18x+36

now, we can combine like terms


50=-14x+8


-14x=42

now, we can solve for x

and we get


x=-3...........Answer

User Swato
by
5.9k points